Utilizing of black cumin (Nigella sativa) flour to increase the immunity system of tilapia (Oreochromis niloticus) against Aeromonas hydrophila bacteria attack - Norma Rizki Silviana; Rosidah; Wahyuniar Pamungkas; Roffi Grandiosa (Jurnal Akuakultur Indonesia)
ABSTRACT